Inquiry into life - Sylvia Mader; Michael Windelspecht (New York : McGraw-Hill Education, 2020)
Dr. Sylvia Mader$1 (Bs text, Inquiry into Life, was originally developed to reach out to science-shy students. The text now represents one of the cornerstones of introductory biology education. Inquiry into Life was founded on the belief that teaching science from a human perspective, coupled with human applications, would make the material more relevant to the student. This text, along with the Inquiry Into Life 15.1 edition, represent an ongoing project in the development of a continuously-updated textbook. As scientists and educators, the authors of this text are well aware that scientific discovery is a dynamic process. Fortunately, the advances in digital publishing are allowing authors to update content on an ongoing basis, which in turn is promoting the ability to update content on a regular basis. This text represents the prototype of those effortss
Keywords: Life